Flexible content authorization using digital rights management in cloud computing / Ali Hussain - Ali , Hussain (2021)
Cloud storages are popular for storing the user’s data. For the storage provider, complying with all aspects of user privacy agreement and safeguarding the user’s personal data is tough. In order to protect the data from security breaches and unauthorized access, Digital Rights Management (DRM) is used for controller access. Applying DRM enable content author of data to have more control over its published or shared content. The use of Cloud storage is common and therefore it is important to improve DRM technology to apply the copyrights policies over Cloud data. This is also important in protecting user’s content and providing addition data integrity and intellectual property protection feature as provided by Cloud storage platform. In easy online redistribution model, even authorized user can download the file from Cloud Storage and could easily republish it without prior permission. However, this can pose threat to Intellectual property, may violate copyright policy and may infringe public reputation by propagating false information. This problem is mainly due to the open and inclusive nature of Internet. And more prominent in online social media platform due to their flexible sharing feature which can make false information viral in negligible time. Digital Rights Management (DRM) tends to solve this problem by leveraging more access control to authors of content. Complex encryptions make DRM service difficult to achieve flexibility, interoperability, Cloud deployment and efficient serving. DRM pertains to solve the issue via strong encryption but most DRM authorization mechanisms directly depending on public-key certificates are relatively less suitable to the Cloud. This study presents a review of Cloud DRM technologies available, their features and limitations. This study also represents Macaroons as an alternative method for temper proof and flexible sharing of data over distributed computing. The study demonstrates that the proposed method can provide the immutable data integrity protection with flexible policy definition to limit the access. The integrity of data is verified with the use of HMAC algorithm chain using the verify function of versifier in Macaroon. The study also presents comparison on Macaroon DRM with related studies and performance benchmarking. The proposed method can be added on top of any Cloud storage's and server to achieve controlled sharing in Cloud DRM. The proposed method is found to be flexible, platform independent and easy integration with third party for controlled sharing with an possible unlimited set of authorization conditions.